Workplace Values and Organizational Commitment of Basic Education Teachers in Catholic Schools - Socorro Carmen B. Importante; Johnny T. Roberto (Philippine Social Science Journal, 2020)
One of the basic essential questions that many thinkers ask is whether values are teachable or not. Values essentially play a significant role in people's behavior, attitudes, perceptions, and motivations. Accordingly, these are manifested in the practice of their work. In this context, the workplace values are concerned with an individual's belief towards performance and evaluative standards relative to their professional duties and responsibilities. The fact that the integration of these values is the best predictor of organizational commitment. In the Diocesan schools of Antique, the teachers seem to have inadequately assimilated and minimally imbibed the practice of Christian and work values, which compromise their commitment to the profession. Thus, the paper assessed the practice of workplace values and the degree of organizational commitment of basic education teachers in Antique Diocesan Catholic Schools (ADCS) for the School Year 2019-2020. Likewise, it determined the difference in the two variables when teachers were grouped according to their age, sex, length of service, and educational attainment. Also, it analyzed the correlation between their practice of workplace values and the degree of organizational commitment.